Contributions of Qualitative Research in Informing HIV/AIDS Interventions Targeting Black MSM in the United States. Issue 6 (23rd July 2016) - Wilson, Patrick A.; Valera, Pamela; Martos, Alexander J.; Wittlin, Natalie M.; Muñoz-Laboy, Miguel A.; Parker, Richard G.
Abstract : This article presents a systematic review of qualitative studies focusing on human immunodeficiency virus (HIV) and acquired immune deficiency syndrome (AIDS) among Black men who have sex with men (BMSM) in the United States. We reviewed studies that were published between 1980 and 2014. Qualitative methods employed in the studies reviewed include in-depth interviews, focus groups, participant observation, and ethnography. We searched several databases (PubMed, PsychINFO, JSTOR, ERIC, Sociological Abstracts, and Google Scholar) for relevant articles using the following broad terms: "Black men" "Black gay/bisexual" or "Black men who have sex with men, " and "qualitative" and/or "ethnography." We include 70 studies in this review. The key themes observed across studies were (1) heterogeneity, (2) layered stigma and intersectionality, (3) risk behaviors, (4) mental health, (5) resilience, and (6) community engagement. The review suggests that sexual behavior and HIV-status disclosure, sexual risk taking, substance use, and psychological well-being were contextually situated. Interventions occurring at multiple levels and within multiple contexts are needed to reduce stigma within the Black community. Similarly, structural interventions targeting religious groups, schools, and health care systems are needed to improve the health outcomes among BMSM. Community engagement and using community-based participatory research methods may facilitate the development and implementation of culturally appropriate HIV/AIDS interventions targeting BMSM.